Aging and dependency in Brazil: the overlapping of class, race/ethnicity, and gender - Miranda, Líbia Mafra Benvindo de; Teixeira, Solange Maria (Argumentum, 2025)
This article analyses aspects of old age dependency within the marginalised and invisible working class, and its connection to the complexity of social relations of class, race/ethnicity and gender, to highlight that the social production of old age is found in the materiality of the lives of men and women. This is theoretical work with a bibliographic and documentary basis, based on critical literature, particularly that of a Marxist nature. The discussion is founded on critical gerontology and dependency based on the overlapping of particularities of class, race/ethnicity, and gender. It concludes that capitalist society, with its division of classes and the exploitation of one by the other, intertwined with racism and sexism, form a symbiotic “knot” that expands and reproduces social inequities that impact old age.